2015
DOI: 10.1055/s-0035-1549429
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic Sacral Fracture in Late Pregnancy: A Case Report

Abstract: Study Design Case report. Objective Sacral fractures, traumatic or atraumatic, are a rather rare cause of low back pain. The majority of the cases of pregnancy-related sacral fractures are reported as a postpartum complication, and only few cases of sacral atraumatic fractures have been reported in the last trimester of the pregnancy. The aim of this study is to report a rare case of atraumatic sacral fracture in the third trimester of pregnancy. Methods We report the case of a 30-year-old Caucasian European w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(26 reference statements)
0
11
0
1
Order By: Relevance
“…Often, fatigue fractures will show surrounding marrow edema with formal radiographic evidence of the fracture only becoming apparent within 1 month of the onset of symptoms (Figure 1). We and others have shown that CT and x-rays lack the appropriate resolution to isolate such fractures and pose teratogenic risks to the fetus [7,1113,16,17,20]. Exclusion of pregnancy associated osteoporosis is also required by means of formal bone densitometry and fasting metabolic biochemical assessments [7,15–17,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, fatigue fractures will show surrounding marrow edema with formal radiographic evidence of the fracture only becoming apparent within 1 month of the onset of symptoms (Figure 1). We and others have shown that CT and x-rays lack the appropriate resolution to isolate such fractures and pose teratogenic risks to the fetus [7,1113,16,17,20]. Exclusion of pregnancy associated osteoporosis is also required by means of formal bone densitometry and fasting metabolic biochemical assessments [7,15–17,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, atraumatic stress fractures of the sacrum arising intrapartum or during the early postpartum are unusual and rare complications of pregnancy. To date, only a handful of cases having been reported across North America [57], Europe [813], the Middle East [14–19], and South Korea [20]. These fractures are classified as either insufficiency or fatigue fractures [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue fractures occur in healthy bones under abnormal stresses, while the latter occurs in weakened bones under normal stresses. Sacral stress fractures are mostly seen in athletes, especially long-distance runners, due to unusual loads with repetitive activity [5]. Sacral fatigue fractures have been reported in athletes and during postpartum and intrapartum periods most of which were related to excessive weight gain, hyperlordosis, pelvic ligament weakness and osteopenia during pregnancy, whereas insufficiency fractures have been mostly reported in the elderly postmenopausal osteoporotic patients [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…B. Läufer) und das weibliche Geschlecht Stressfrakturen vermuten [81,82]. Als differenzialdiagnostische Besonderheit sind schwangere Patientinnen zu erwähnen, die ebenfalls Stressfrakturen im Becken aufweisen können [18,83].…”
Section: Diskussionunclassified